ERADICATING SEXUAL ABUSE AND GENDER BASED VIOLENCE IN AFRICA AND AMERICA: ROLE OF RELIGIOUS LEADERS - Ushe Mike Ushe (European Scientific Journal, ESJ, 2015)
This paper examines the responsibility of religious leaders in protecting sexual and gender based violence in Africa and America. The paper adopted a qualitative approach that utilized secondary sources and participant observation method in gathering and analysing of data. The paper observed that sexual and gender violence is endemic in Africa and American societies. The paper recommends among others, that the government should formulate policies that would both guide against sexual harassment and gender based violence as well as empowers women to participate actively in the formulation of policies and governance in Africa and America.